PENERAPAN PRINSIP-PRINSIP SYARIAH PADA SHARIA ONLINE TRADING SYSTEM MENURUT FATWA DEWAN SYARI’AH NASIONAL NO.80/DSN-MUI/III/2011 - Agustin, Inneke Wahyu (IAIN Tulungagung, 2019)
SOTS is the first online sharia trading system in the world and was formed with great hopes that the majority of Muslim community of Indonesia can contribute a lot to the Capital Market in Indonesia. This system is based on sharia principles as DSN-MUI Fatwa No. 80 of 2011. Some people are skeptical about SOTS because they think it is still jointly managed with the Online Trading System. The focus of this study is to analyze the Sharia Online Trading System based on the DSN-MUI Fatwa No.80 of 2011. Using the literature review method based on data on the official website. The results of the analysis state that SOTS is in accordance with the sharia principles. However, because there is still a scope of orders from the online trading system, people are doubtful that it is not in accordance with Islamic principles.Keywords: Sharia Principles, Sharia Online Trading System (SOTS), Sharia Capital Market